Bakteri Termofil Penghasil Selulase Asal Sumber Air Panas di Indonesia - megahati, Ruth (Jurnal Bioconcetta, 2017)
The thermo-alkaliphilic (the bacteria can live and grow in hot environment was famous as termophilic bacteria with temperature around 45o-50o with high pH that was 8,4-9,5) which produced cellulose enzyme has been product commercial by some global industry and many of them was used in food, woof, fuel, paper industry, and textile. The purpose of this research was to get thermo-alkaliphilicÂ  bacteria isolate and know the activity of thermo-alkaliphilic bacteria qualitatively. The sample taken of hot spring in 3 points with purposive method based on pH. First hot spring (S1) 48oC with pH 8,7, second (S2) 490C with pH 8,6, third (S3) 50oC with pH 8,5. The research procedure was preparation (sterilization tools and medium, medium made NA, and Cellulosic selective, making kultur stock), puring the bacteria, cellulosic testing activity and research observation. The result was found 10 thermo-alkaliphilic bacteria isolate which able to live in 50oC and 5 isolates bacteria was able to degradation CMC. S2.2 isolate has the biggesst cellulosic index was 2,90 mm and S3.1 isolate has smallest cellulosic index was 0,52 mm